INOVASI SISTEM PENDIDIKAN PONDOK PESANTREN - Dedi Sahputra Napitupulu (Jurnal Al-Fatih, 2018)
In Indonesia, the seminary became the most rightful heirs over the scientific literature is the corpus of Islam. This expression is really reasoned, at least there is the inherent self cultur pesantren which to this day still consistently maintained classical text or commonly known as the ‘Yellow Book’ remains taught. Boarding school to this day still are believed by most Muslims as Islamic institutions which are able to create integration between science and religion knowledge. At the same time boarding school also became the only hope to be able to understand and protect rigid and erroneous doctrine that flourished in the midddle of new modernization. That's why the existence of boarding school is urgently needed. With the use of field research, the following description will to try presents the innovations undertaken by Seminary Ar-Raudhatul Hasanah from the educational system.